The wrath of God? - Abd Razak, Dzulkifli (2005)
The carnage caused by Hurricane Katrina may be another opportunity for the US to make amends without attempting to play God again. "THE death toll is expected to rise sharply from Gulf Coast towns and cities. A massive searchandrescue situation is still going on. We believe there are hundreds more out there." In one Gulf coast city alone, "30 deaths occurred in a single apartment complex", according to a local emergency services spokesperson. There were also reports of looting, breakins, rape and orders to shoottokill. Shortage of fresh water, food and electricity are rampant. Highways, roads and other forms of communications have been shut down. Patients are dying for the lack of treatment and medication, including oxygen and intravenous fluids. Tens of thousands had to be evacuated to overcrowded temporary squalid shelters in the sweltering heat.